Comparative Evaluation of Serum Separator V-Tube™, VQ-Tube™, and K2EDTA V-Tube™ with Becton Dickinson Tubes for Chemistry, Immunology, and Hematology Examinations - Takho Kang; Seung Gyu Yun; Myung-Hyun Nam; Yunjung Cho; Minjeong Nam (Diagnostics, 2025)
Background: Rigorous evaluation of vacuum blood collection tubes is essential to ensure the reliability of laboratory results. Methods: In this study, we compared the serum separator tube V-Tube™ (V-Tube SST), the quick-clotting serum separator tube VQ-Tube™ (VQ-Tube SST), and the K2EDTA V-Tube™ (V-Tube K2EDTA) manufactured by AB Medical (Seoul, Republic of Korea), with their respective counterparts from Becton Dickinson (BD, Franklin Lakes, NJ, USA): BD Vacutainer® SST™ II Advance Tube (BD SST) and BD Vacutainer® K2EDTA 5.4 mg Tube (BD K2EDTA). The evaluation encompassed 61 measurands across the fields of chemistry, immunology, and hematology, and incorporated a stability assessment for the VQ-Tube SST. Results: The V-Tube SST, VQ-Tube SST, and V-Tube K2EDTA demonstrated comparable analytical performance to the BD tubes for the majority of measurands. However, glucose, lactate dehydrogenase, mean corpuscular volume, and mean corpuscular hemoglobin concentration indicated clinically significant differences according to the desirable biological variation database (Ricos). Conclusions: These findings suggest that, while the V-tube and VQ-tube SST generally serve as alternatives to BD tubes, caution should be taken when interpreting results for specific measurands that demonstrated clinically significant discrepancies.